Neutral zone or conventional implant-retained overdentures? an assessment on quality of life, denture stability, patient satisfaction and maintenance requirements - Buse Cebi Gul; Murat Doğuş Günel; Tan Fırat Eyüboğlu; Mutlu Özcan (BMC Oral Health)
Abstract Purpose This study evaluated whether implant-retained overdentures fabricated using the neutral zone (NZ) technique offer superior long-term oral health related quality of life (OHRQoL) outcomes compared to conventional overdentures (CO) and assess the influence of these techniques on denture stability, patient satisfaction, and maintenance requirements. Materials and methods This study involved 29 edentulous patients (14 in the NZ group and 15 in the CO group) who received mandibular implant-retained overdentures with a minimum two year follow up. Two implants were placed in the mandible for each patient, and overdentures were fabricated using either conventional methods or the neutral zone concept, all performed by the same clinician and technician. The OHIP-EDENT questionnaire assessed functional, physical, psychological, and social aspects. Statistical analyses compared pre and post treatment scores as well as intergroup differences. Results Both groups demonstrated significant post-treatment improvement in OHRQoL (p < 0.001). However, no statistically significant difference was observed between the NZ and conventional groups in overall satisfaction, functional outcomes, pain reduction, or psychological and social well-being (p > 0.05). Furthermore, no significant difference was found in prosthesis fracture rates or the frequency of locator replacements (p > 0.05). Conclusions Implant-retained overdentures, regardless of fabrication technique, significantly improved patient reported outcomes. However, the NZ technique did not provide a significant advantage over the conventional technique in long term OHRQoL or prosthodontic maintenance.